Do ambient urban odors evoke basic emotions? - Glass, Sandra T.; Lingg, Elisabeth; Heuberger, Eva (Frontiers in Psychology, 2014)
Fragrances, such as plant odors, have been shown to evoke autonomic response patterns associated with Ekman's (Ekman et al., 1983) basic emotions happiness, surprise, anger, fear, sadness, and disgust. Inducing positive emotions by odors in highly frequented public spaces could serve to improve the quality of life in urban environments. Thus, the present study evaluated the potency of ambient odors connoted with an urban environment to evoke basic emotions on an autonomic and cognitive response level. Synthetic mixtures representing the odors of disinfectant, candles/bees wax, summer air, burnt smell, vomit and musty smell as well as odorless water as a control were presented five times in random order to 30 healthy, non-smoking human subjects with intact sense of smell. Skin temperature, skin conductance, breathing rate, forearm muscle activity, blink rate, and heart rate were recorded simultaneously. Subjects rated the odors in terms of pleasantness, intensity and familiarity and gave verbal labels to each odor as well as cognitive associations with the basic emotions. The results showed that the amplitude of the skin conductance response (SCR) varied as a function of odor presentation. Burnt smell and vomit elicited significantly higher electrodermal responses than summer air. Also, a negative correlation was revealed between the amplitude of the SCR and hedonic odor valence indicating that the magnitude of the electrodermal response increased with odor unpleasantness. The analysis of the cognitive associations between odors and basic emotions showed that candles/bees wax and summer air were specifically associated with happiness whereas burnt smell and vomit were uniquely associated with disgust. Our findings suggest that city odors may evoke specific cognitive associations of basic emotions and that autonomic activity elicited by such odors is related to odor hedonics.